CONSTRUCT GUARD - R, Priyanka (PEOPLE: International Journal of Social Sciences, 2024)
Construction sites still have safety issues, which has led to the creation of cutting-edge. The Proposed Solution is Smart wearable bands and helmets equipped with a variety of sensors for tracking employee health and safety. The technology, which is supported by a connected wearable belt, continuously tracks worker location and health parameters. An advanced accelerometer detects workers’ standing positions, triggering instant notifications to contractors in the event of dizziness. A Spo2 sensor enhances total health surveillance by monitoring oxygen and pulse rates in addition to the foregoing. This proposed system transcends traditional safety protocols, presenting a dynamic and proactive approach to worker well-being. By leveraging advanced sensor technologies and location-based intelligence, our smart wearables provide real-time health insights and prompt alerts during health compromises or accidents.